Students’ Voice in ICT-Enhanced Learning in English as a Foreign Language (EFL) Classroom: Benefits and Challenges - Laxmi Mustika Cakrawati; Indrie Setya Lestari (Jurnal Vokasia, 2025)
In an effort to cope with the challenges and requirements of the 21st century education, due to the rapid advancement of technology, teachers are required to integrate ICT in their classroom. This study attempts to investigate students’ voice in ICT-enhanced learning in English as a Foreign Language (EFL) classrooms, focusing on the benefits and challenges. The study involved 100 high school students from some schools in Bandung, West Java, Indonesia. The data were obtained from a questionnaire and interview and were analyzed by using a mixed-method approach. The questionnaire, which consists of closed-ended questions using the Likert scale, was administered to students to explore their voice while the interview was conducted to gain in-depth opinion on the ICT use in the classroom. The participants of the study showed various responses toward the use of technology in the EFL classroom. The findings reveal that many teachers have integrated ICT into their classroom. Although slow-speed internet and school facilities are considered as the main challenges in ICT use, the results of the study indicate that a technology-rich environment can motivate students and promote a learner-centered classroom. Therefore, based on the findings, it is suggested that teachers effectively and creatively explore ICT-enhanced learning to engage students, who are considered as digital natives, in meaningful learning experiences.